THE EFFECT OF DEBT POLICY ON COMPANY VALUE IN THE PULP AND PAPER SUB SECTOR LISTED ON BEI - alfin akuba (Journal of Applied Sciences, Management and Engineering Technology, 2021)
This study aims to determine and analyze how much influence the Debt Policy (X) partially affects Firm Value (Y). This research is a quantitative study, using ratio analysis. The analysis method uses simple linear regression. The results showed that the Debt Policy (X)) partially did not have a significant effect on Firm Value (Y) in the Pulp and Paper sub-sector that went public on the Indonesia Stock Exchange of 0.449. Keywords: Debt Policy and Company Value